2019
DOI: 10.1016/j.jsams.2019.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Rowers with a recent history of low back pain engage different regions of the lumbar erector spinae during rowing

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 31 publications
2
31
1
Order By: Relevance
“…In line with previous studies, the lower grids were attached 5 cm lateral to the lumbar spinous processes, beginning at the level of L5 (Falla et al, 2014;Martinez-Valdes et al, 2019;Sanderson et al, 2019). The upper grids remained 5 cm lateral to the spinous processes; however, the inferior border was affixed to the skin 5 mm cranial to the superior border of the lower grid (Figure 2).…”
Section: Experimental Set-upsupporting
confidence: 74%
See 2 more Smart Citations
“…In line with previous studies, the lower grids were attached 5 cm lateral to the lumbar spinous processes, beginning at the level of L5 (Falla et al, 2014;Martinez-Valdes et al, 2019;Sanderson et al, 2019). The upper grids remained 5 cm lateral to the spinous processes; however, the inferior border was affixed to the skin 5 mm cranial to the superior border of the lower grid (Figure 2).…”
Section: Experimental Set-upsupporting
confidence: 74%
“…As described previously, the location of the centroid in the x-and y-axes was calculated from these topographical maps (Tucker et al, 2009;Falla et al, 2017;Sanderson et al, 2019). Additionally, values for the complexity (entropy) of the signals were calculated for each epoch, this measure indicates how homogenous the contraction was across the measured area, with a reduction in this value indicating a more heterogeneous contraction (Martinez-Valdes et al, 2019). The RMS and entropy were averaged across the large grids to obtain one value for each side.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature concerning sEMG applications in sports is very extensive and focused on physiology ( 191 , 192 ) training, prevention of injury, and recovery after injury (in particular the anterior cruciate ligament injury ( 193 ). Many sports have been investigated, in particular golf ( 194 ), jumping ( 195 ), cycling ( 196 ), sprinting ( 197 ), volleyball ( 198 ), but also strength training ( 199 , 200 ), back pain in rowers ( 201 ), patellofemoral pain ( 170 , 202 ), and aging ( 59 , 203 ). The distribution of muscle fiber conduction velocity, related to fiber diameter, may provide insight in muscle structure.…”
Section: Surface Emg Applicationsmentioning
confidence: 99%
“…Martinez-Valdes et al concluded an inefficient activation of the erector spinae in rowers with LBP due to higher activation of the erector spinae and a less complex EMG signal [18]. Further, rowing is characterised by high frequent bending of the lumbar spine [19], which possibly affects LBP or vice versa [20,21].…”
Section: Introductionmentioning
confidence: 99%